Analisis Kontribusi Pajak Bumi dan Bangunan Sektor Pedesaan dan Perkotaan (PBB-P2) Pada Pendapatan Asli Daerah Nagan Raya - Fadli Zuwanda; Sari Maulida Vonna; Fikri Yusdarli (Akbis: Media Riset Akuntansi dan Bisnis, 2022)
An area is able to explore sources of Regional Original Income. whether it comes from regional fees, regional retributions, the results of wealth management having separate areas and other legitimate regional original income can be seen in Regional Original Income (PAD). Taxes are people's contributions to the state treasury, based on regulations that can be applied without obtaining mutual benefits, and taxes are used to pay general expenses. This type of research is descriptive quantitative research. The tax that is replaced from the central contribution to the regional contribution only represents PBB-P2 in the rural and urban sectors (P2). Meanwhile PBB-P2 in the fields of forestry, rice fields and investigations (P3) continues to be the central contribution. The PBB-P2 transition has been carried out since 2011. The purpose of the PBB-P2 transfer is to strengthen the local tax authority in the Regency or City. The data collection techniques used in this study are primary data and secondary data. Data analysis uses data provided from the Nagan Raya Revenue Sector BPKD office related to Land and Building Taxes and Regional Original Income in Nagan Raya. The results of the analysis of the acquisition of land and building taxes, the Nagan Raya Regional Revenue Sector have succeeded in realizing the building land tax in accordance with the target or even increasing than the target land tax that has been set.